CULTURAL EXPRESSIONS IN PARENTING: FIGURATIVE LANGUAGE IN THE CIA-CIA LANGUAGE FOR EDUCATING CHILDREN IN WABULA DISTRICT - Zamha Zamihu, Juamdan; Saifullah, Saifullah (English Education Department, 2025)
This qualitative study explores the role of cultural expressions, specifically figurative language in the Cia-Cia language, used by parents to educate their children in Wabula District, Buton Regency. The study aims to identify (1) the types of figurative expressions embedded in daily parent-child communication and (2) their influence on children's cognitive development. Data were gathered through naturalistic observation and semi-structured interviews with four parents who frequently use Cia-Cia in household interactions. The findings reveal that similes, hyperboles, idioms, and personifications are commonly used—often unconsciously—to communicate values, emotions, and abstract concepts. These figurative expressions not only enrich the children’s linguistic input but also facilitate imagination, critical thinking, and the internalization of cultural norms. The study highlights the educational potential of local language expressions in fostering both cognitive growth and cultural identity. Increasing parental awareness of the pedagogical power of figurative language could enhance intentional teaching practices within local cultural contexts